Ensuring ethical animal welfare research: Are more ethics review committees the solution? - Nielsen, Birte L.; Golledge, Huw D. R.; Chou, Jen-Yun; Camerlink, Irene; Pongrácz, Péter; Ceballos, Maria Camila; Whittaker, Alexandra L.; Olsson, I. Anna S. (Peer Community Journal, 2023)

(untitled)
[This article has no abstract]